A fluorescent temperature measuring material and preparation method for biological window
By co-doping CaIn2O4 phosphor on the biological window, using Yb3+/Tm3+/RE3+(Er, Ho) to measure temperature using the down-conversion fluorescence principle, the accuracy and interference problems of the traditional method are solved, and high sensitivity and high resolution are achieved. biological window temperature measurement.
Patent Information
- Application Number
- CN202310645824.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-02
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-06-02
AI Technical Summary
Traditional biological window temperature measurement methods are susceptible to the environment and interfere with biological samples, reducing measurement accuracy and reliability, and unable to meet the needs of high precision and high resolution.
Using Yb3+/Tm3+/RE3+ (Er, Ho) based on the downconversion fluorescence principle, the temperature information is obtained by measuring the fluorescence intensity changes. The material design is 10% Yb3+/0.2% Tm3+/x%Er3+ or 10 The co-doped structure of %Yb3+/0.2%Tm3+/x%Ho3+ is prepared in combination with sol-gel method and sintering process, and has photodamage resistance and biocompatible.
It realizes high sensitivity and high resolution temperature measurement, has fast response and deep tissue penetration, and is suitable for temperature detection in organisms, reduces biological background fluorescence interference, and improves temperature measurement accuracy and reliability.
Smart Images

Figure CN116904188B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of rare earth (RE) down-conversion fluorescence temperature measurement sensing applied to biological windows, and specifically relates to a fluorescence temperature measurement material applied to biological windows and a preparation method thereof. Background Art
[0002] Temperature measurement is a common requirement in biological research and clinical treatment, especially for biological windows, which require high-precision and high-resolution temperature measurement methods. Traditional temperature measurement methods cannot meet this requirement because they are usually susceptible to environmental influences and may interfere with biological samples during the measurement process, reducing measurement accuracy and reliability. These problems require an innovative solution. Summary of the invention
[0003] The present invention provides a down-conversion fluorescence temperature measurement material and a preparation method for use in a biological window. The material is based on the principle of down-conversion fluorescence. When excited by a laser, the material emits fluorescence of a specific wavelength, and the fluorescence intensity is closely related to the temperature. Therefore, by measuring the change in fluorescence intensity, the temperature change information of the sample can be obtained.
[0004] On the other hand, a method for preparing a fluorescent temperature measurement material for use in a biological window is also provided.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a fluorescent temperature measuring material for a biological window, the method comprising: weighing Yb2O3, Tm2O3, and RE2O3 powders in molar ratio, wherein RE is Ho or Er, and the molar ratio satisfies: 10% Yb 3+ / 0.2%Tm 3+ / x%Er 3+ , x=1,2,3,4; or 10% Yb 3+ / 0.2%Tm 3+ / x%Ho 3+ , x=0.1,0.3,0.5,0.7;
[0007] Each component is mixed with nitric acid to prepare Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions;
[0008] Weigh CaCO3 and In(NO3)3〃4.5H2O and mix them in a beaker, then drop Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions and stir;
[0009] Add complex citric acid and dilute with deionized water;
[0010] The liquid was dried and evaporated to obtain a yellow dry gel, which was ground in an agate mortar with alcohol for 1 hour. The ground powder was transferred to a ceramic crucible and placed in a high-temperature box-type electric furnace for calcination in two temperature stages.
[0011] Furthermore, the concentrations of Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions are respectively: 0.1 mol / L Yb(NO3)3, 0.01 mol / L Tm(NO3)3, 0.01 mol / L Ho(NO3)3, or 0.05 mol / L Er(NO3)3.
[0012] Further, when RE = Er, x = 1, the mass ratio of the weighed CaCO3 to In(NO3)3〃4.5H2O and citric acid is 0.2942:2.1197:3.7065, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2942:2.9397:0.5879:0.5879;
[0013] When RE=Er, x=2, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2938:2.1053:3.7008, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2938:2.93521:0.5870:1.1741;
[0014] When RE=Er, x=3, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2933:2.0908:3.6951, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2933:2.93070:0.5861:1.7584;
[0015] When RE=Er, x=4, the ratio of the weighed CaCO3 mass to In(NO3)3〃4.5H2O and citric acid is 0.2929:2.0765:3.6895, and the mass volume ratio g / ml of the added Yb(NO3)3, Tm(NO3)3 and RE(NO3)3 solutions is 0.2929:2.92620:0.5852:2.3410.
[0016] Further, when RE=Ho, x=0.1, the mass ratio of the weighed CaCO3 to In(NO3)3〃4.5H2O and citric acid is 0.2946:2.1328:3.7717, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2946:2.9438:0.5888:0.2944;
[0017] When RE=Ho, x=0.3, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2945:2.1299:3.7106, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, RE(NO3)3 solution is 0.2946:2.9430:0.5886:0.8829;
[0018] When RE=Ho, x=0.5, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2944:2.1271:3.7095, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2944:2.9421:0.5884:1.4711;
[0019] When RE=Ho, x=0.7, the ratio of the weighed CaCO3 mass to In(NO3)3〃4.5H2O and citric acid is 0.2943:2.1242:3.7084, and the mass volume ratio g / ml of the added Yb(NO3)3, Tm(NO3)3 and RE(NO3)3 solutions is 0.2943:2.9412:0.5882:2.0589.
[0020] Furthermore, the two temperature stages are: preheating and then sintering in the intelligent ceramic fiber muffle furnace, the temperatures are set to 500°C and 1300°C, and the times are set to 3h and 6h, respectively.
[0021] A fluorescent temperature measuring material for biological windows, wherein the temperature measuring material comprises 10% Yb 3 + / 0.2%Tm 3+ / x%Er 3+ , x=1,2,3,4; or 10% Yb 3+ / 0.2%Tm 3+ / x%Ho 3+ , co-doped CaIn2O4 phosphors with x=0.1, 0.3, 0.5, 0.7.
[0022] The beneficial effects of the present invention include:
[0023] The material has the following characteristics: (1) sensitivity and high resolution; (2) resistance to light damage and biocompatibility; (3) easy preparation and use, and suitable for various biological windows.
[0024] A new technology material was proposed to address the phenomenon of biological autofluorescence; Yb 3+ / Tm 3+ / RE 3+ (Er, Ho) co-doped CaIn2O4 phosphor is a thermally enhanced fluorescent temperature measurement material used in biological windows, which can be used to develop biological fluorescent probes based on fluorescence intensity ratio. The fluorescence intensity ratio technology based on rare earth ion energy levels has the advantages of fast response, high sensitivity and spatial resolution, and has quickly become a research hotspot in the field of temperature detection. Compared with traditional fluorescent temperature probe materials, rare earth doped down-conversion temperature measurement materials have broad development potential in temperature detection in biological tissues or cells due to their excellent luminescence properties, low toxicity, low biological background fluorescence interference, and deep tissue penetration.
[0025] In view of the interference of biological background fluorescence and the inability to penetrate biological tissues deeply, the current situation that the requirements for the use of fluorescence temperature measurement technology cannot be met in vivo is solved through reasonable experimental design in the near-infrared band, thus effectively solving the temperature detection problem in biological tissues or cells; specifically, under 980nm excitation, the temperature sensing characteristics of this fluorescent temperature measurement material were tested (in 10% Yb 3+ As a sensitizer, 3% Er was doped as an activator. 3+ / 0.5%Ho 3+ ), Figure 7 (a) CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 3%Er 3+ 3D mapping of the down-conversion band projection of the sample in the temperature range of 303 to 493 K. At the same pump power, Er 3+ The ion intensity near 1550nm ( 4 I 13 / 2 → 4 I 15 / 2 ) and Yb3+ ions around 1000-1100nm ( 2 F 5 / 2 → 2 F 7 / 2 ) The emission intensity increases with increasing temperature. Studies have shown that CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 3%Er 3+ The sample produced a phenomenon of thermal enhancement of luminescence. Figure 7(b) CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 3%Er 3+ Normalized spectra of the samples in the temperature range of 303 to 493 K. Figure 8 (a)-(f) are CaIn2O4:10%Yb 3+ / 0.2%Tm 3 + / 3%Er 3+ In the range of 303 to 493K, FIR, S A , S R picture. Fig. 9 (a) CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 0.5%Ho 3+ 3D mapping of the down-conversion band projection of the sample in the temperature range of 303 to 493 K. At the same pump power, Ho 3+ The ion intensity near 1200~1250nm ( 5 I6→ 5 I8) and Yb3+ ions are around 1000-1100nm ( 2 F 5 / 2 → 2 F 7 / 2 ) The emission intensity increases with increasing temperature. Studies have shown that CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 0.5%Ho 3+ The sample produced a phenomenon of thermal enhancement of luminescence. Figure 7 (b) CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 0.5%Ho 3+ Normalized spectra of the samples in the temperature range of 303 to 493 K. Fig.10 (a)-(c) are CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 0.5%Ho 3+ In the range of 303 to 493K, FIR, S A , S R picture. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A flow chart of preparing materials by the sol-gel method provided in an embodiment of the present invention;
[0027] Figure 2 A flow chart of the down-conversion spectrum of the CaIn2O4 phosphor provided in an embodiment of the present invention;
[0028] Figure 3 XRD spectrum of CaIn2O4 provided in the embodiment of the present invention: (a) is x% Er 3+ / 0.2%Tm 3+ / 10%Yb 3+ XRD pattern of (b) x%Ho 3+ / 0.2%Tm 3+ / 10%Yb 3+ XRD pattern of
[0029] Figure 4 The Rietveld refinement diagram of CaIn2O4 provided in the embodiment of the present invention: (a) 3% Er 3+ / 0.2%Tm 3+ / 10%Yb 3+ XRD pattern of (b) 0.5% Ho 3+ / 0.2%Tm 3+ / 10%Yb 3+ XRD pattern; the inset is a schematic diagram of the crystal structure of orthorhombic CaIn2O4;
[0030] Figure 5 SEM structure diagram of CaIn2O4 provided in the embodiment of the present invention: (a) 3% Er 3+ / 0.2%Tm 3+ / 10%Yb 3+ XRD pattern of (b) 0.5% Ho 3+ / 0.2%Tm 3+ / 10%Yb 3+ XRD pattern of
[0031] Figure 6 Fourier transform infrared spectrum of CaIn2O4 provided in the embodiment of the present invention: (a) 3% Er 3+ / 0.2%Tm 3 + / 10%Yb 3+ XRD pattern of (b) 0.5% Ho 3+ / 0.2%Tm 3+ / 10%Yb 3+ XRD pattern of
[0032] Figure 7 3D mapping diagram and normalized curve provided for the embodiment of the present invention: (a) CaIn2O4: 3% Er 3+ / 0.2%Tm 3 + / 10%Yb 3+3D mapping diagram of the relationship between the down-conversion emission peak and temperature at 303-493K; (b) CaIn2O4: 3% Er 3+ / 0.2%Tm 3+ / 10%Yb 3+ Normalized curves of phosphor at 1000-1200nm, 1500-1650nm, 1085nm, 1500nm, 1570nm and 1650nm with temperature in the range of 303-493K;
[0033] Figure 8 FIR, SA, SR graphs and temperature sensing graphs provided by the embodiments of the present invention: (a)-(f) are CaIn2O4:3%Er 3 + / 0.2%Tm 3+ / 10%Yb 3+ FIR, SA, and SR diagrams at 303-493 K. (a)-(c) are temperature sensing based on non-thermal coupling energy levels; (d)-(f) are temperature sensing based on thermal coupling energy levels.
[0034] Fig. 9 3D mapping diagram and normalized curve provided by the embodiment of the present invention, (a) CaIn2O4: 0.5% Ho 3+ / 0.2%Tm 3+ / 10%Yb 3+ 3D mapping diagram of the down-conversion emission peak and temperature relationship at 303-493K; (b) CaIn2O4: 0.5% Er 3+ / 0.2%Tm 3+ / 10%Yb 3+ Normalized curves of phosphor at 1000-1125nm, 1200-1250nm, 1078nm, and 1158nm with temperature in the range of 303-493K;
[0035] Fig.10 FIR, SA, SR diagrams provided for the embodiments of the present invention, (a)-(c) are for CaIn2O4:0.5%Ho 3+ / 0.2%Tm 3 + / 10%Yb 3+ FIR, SA, and SR plots at 303-493K. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with the accompanying drawings and schematic diagrams of experimental phenomena.
[0037] Figure 1 Yb was synthesized by sol-gel method. 3+ / Tm3+ / RE 3+ (RE=Er,Ho) co-doped CaIn2O4 phosphor flow chart. The experimental raw materials are high-purity Yb2O3, Tm2O3, Ho2O3 and Er2O3 powders weighed in molar ratio. Yb2O3, Tm2O3, RE2O3 powders weighed in molar ratio, where RE is Ho or Er, and the molar ratio satisfies: 10% Yb 3+ / 0.2%Tm 3+ / x%Er 3+ , x=1,2,3,4; or
[0038] 10% Yb 3+ / 0.2%Tm 3+ / x%Ho 3+ , x=0.1,0.3,0.5,0.7;
[0039] Each component is mixed with nitric acid to prepare Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions;
[0040] Weigh CaCO3 and In(NO3)3〃4.5H2O and mix them in a beaker, then drop Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions and stir;
[0041] Add complex citric acid and dilute with deionized water;
[0042] The liquid was dried and evaporated to obtain a yellow dry gel, which was ground in an agate mortar with alcohol for 1 hour. The ground powder was transferred to a ceramic crucible and placed in a high-temperature box-type electric furnace for calcination in two temperature stages.
[0043] The concentrations of Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions are: 0.1 mol / L Yb(NO3)3, 0.01 mol / L Tm(NO3)3, 0.01 mol / L Ho(NO3)3, or 0.05 mol / L Er(NO3)3.
[0044] When RE=Er, x=1, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2942:2.1197:3.7065, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2942:2.9397:0.5879:0.5879;
[0045] When RE=Er, x=2, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2938:2.1053:3.7008, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2938:2.93521:0.5870:1.1741;
[0046] When RE=Er, x=3, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2933:2.0908:3.6951, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2933:2.93070:0.5861:1.7584;
[0047] When RE=Er, x=4, the ratio of the weighed CaCO3 mass to In(NO3)3〃4.5H2O and citric acid is 0.2929:2.0765:3.6895, and the mass volume ratio g / ml of the added Yb(NO3)3, Tm(NO3)3 and RE(NO3)3 solutions is 0.2929:2.92620:0.5852:2.3410.
[0048] When RE=Ho, x=0.1, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2946:2.1328:3.7717, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2946:2.9438:0.5888:0.2944;
[0049] When RE=Ho, x=0.3, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2945:2.1299:3.7106, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, RE(NO3)3 solution is 0.2946:2.9430:0.5886:0.8829;
[0050] When RE=Ho, x=0.5, the mass ratio of CaCO3 weighed to In(NO3)3〃4.5H2O and citric acid is 0.2944:2.1271:3.7095, and the mass volume ratio g / ml to the added Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions is 0.2944:2.9421:0.5884:1.4711;
[0051] When RE=Ho, x=0.7, the ratio of the weighed CaCO3 mass to In(NO3)3〃4.5H2O and citric acid is 0.2943:2.1242:3.7084, and the mass volume ratio g / ml of the added Yb(NO3)3, Tm(NO3)3 and RE(NO3)3 solutions is 0.2943:2.9412:0.5882:2.0589.
[0052] The two temperatures include: preheating and sintering in the intelligent ceramic fiber muffle furnace, the temperature is set to 500℃ and 1300℃, the time is set to 3h and 6h, respectively, and simple grinding after sintering. Finally, Yb 3+ / Tm 3+ / RE 3+ (RE=Er,Ho) co-doped CaIn2O4 phosphor, and its structure, temperature and optical properties were further studied. Figure 2 This is the experimental flow chart of the down-conversion temperature sensing characteristics of CaIn2O4 phosphor, which is mainly composed of 980nm diode laser, λ500 spectrometer, lock-in amplifier, photon counter and computer. XRD and SEM characterize that CaIn2O4 belongs to the orthorhombic system; FTIR characterizes the low phonon energy of CaIn2O4 matrix, which is an excellent material for preparing phosphor; the control accuracy of the temperature sensing characteristics of the prepared material is 0.1℃;
[0053] The present invention prepares a fluorescent temperature measuring material for biological windows. The temperature measuring material contains 10% Yb 3+ / 0.2%Tm 3+ / x%Er 3+ , x=1,2,3,4; or 10% Yb 3+ / 0.2%Tm 3+ / x%Ho 3+ , co-doped CaIn2O4 phosphors with x=0.1, 0.3, 0.5, 0.7.
[0054] The present invention uniformly mixes the liquid raw materials to be doped with elements, and in order to obtain better effects, adds a complexing agent to help the raw materials dissolve better; for the preparation of the colloid, the amount of water added and the heating and stirring time must be strictly controlled, which will directly affect the performance of the final synthetic material; the third step is to turn it into an applicable material through drying and sintering.
[0055] In this embodiment, CaCO3 and In(NO3)3〃4.5H2O were weighed and mixed in a beaker, and Yb(NO3)3, Tm(NO3)3, and RE(NO3)3 solutions were added dropwise and stirred. The amounts of the components are shown in Tables 1 and 2;
[0056] Table 1 (RE = Er 3+ )
[0057]
[0058]
[0059] Table 2 (RE=Ho 3+ )
[0060]
[0061] The obtained product was measured by X-ray diffractometer (Rigaku Ultima IV) for the experimentally prepared Yb 3+ / Tm 3+ / RE 3 + (Er, Ho) co-doped CaIn2O4 phosphor, the radiation source is Cu-Kα rays, the wavelength λ=0.15406nm, and the 2θ angle range is 20-80° (2θ degrees). Figure 4 (a) and (b) show the Yb 3+ XRD spectrum of / Tm3+ / RE3+(Er,Ho) co-doped CaIn2O4 phosphor. It can be seen that the diffraction peaks of the sample correspond one-to-one with the CaIn2O4 standard card (PDF#17-0643) and the spectrum peaks are sharp, indicating that the sample has good crystallinity and that the generated sample is pure phase. 3+ / Tm 3+ / RE 3+ (Er, Ho) ions have been completely doped into the CaIn2O4 matrix lattice. The XRD pattern was refined using GsasII software, and the approximate value of the structural model and the real structure can be estimated from the power intensity distribution measurement value. Because there will be many inevitable errors in the experiment, and the properties of the crystal material itself are also different. Through refinement, that is, adjusting various parameters, the peak size, shape, position, etc. of the reference curve can be changed, and the reference curve and experimental curve are used to calculate the error, so as to obtain the required experimental results. Figure 3 (a, b) shows CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 3%Er 3+ and CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 0.5%Ho 3+ XRD Rietveld refinement results for the sample. The measured, calculated, Bragg positions of the diffraction patterns and the differences between the experimental and calculated diffraction patterns were also investigated in detail. The proposed theoretical adjustments are consistent with this analytical result, where a small difference in the intensity scale close to zero can be observed, as shown by the line (Obs Calc).3+ / 0.2%Tm 3+ / 3%Er 3+ and 10% Yb 3+ / 0.2%Tm 3+ / 0.05%Ho 3+ The sample was subjected to Rietveld refinement, and lattice parameters such as unit cell volume were obtained.
[0062] The crystal data in the Crystallographic Open Database were used as the original model for structure refinement. The calculated values of the refinement results were highly correlated with the actual theoretical values. The space group, unit cell parameters, unit cell volume and feasibility factor are all given in Table 3.
[0063] Table 3
[0064]
[0065] According to the parameters of the XRD Rietveld refinement results, CaIn2O4 belongs to the orthorhombic system. In addition, we imported the refinement results into the VESTA software to draw the unit cell structure diagram of the sample as shown below: Figure 3 Illustration. 2+ 、In 3+ , O -2 All are in the characteristic position. Through query, we know that Er 3+ / Ho 3+ / Tm 3+ / Yb 3+ The ionic radius is And In 3+ The ionic radius is According to crystal chemistry, Er 3+ For example, Er 3+ The ionic radius is Er 3+ WithIn 3+ The ionic radius of Er differs by 11.25%. According to the principle that the radii of the same valence are similar, the present invention believes that when the ionic radius difference is less than 30%, Er 3+ Can better occupy In 3+ lattice position.
[0066] The morphology of the samples was recorded using a JEOL scanning electron microscope (FE-SEM, Quanta 450, FEI). Figure 5 For RE 3+ (Er / Ho, Tm) co-doped CaIn2O4 phosphor SEM image, Figure 5 (a) 3% Er 3+ / 0.2%Tm 3+ / 10%Yb 3+ ; Figure 5(b) 0.5% Ho 3+ / 0.2%Tm 3+ / 10%Yb 3+ It can be found that the sample is composed of regular, smooth crystalline particles with a dumbbell-like morphology and has reached the micrometer level. The prepared particles are almost uniform in size, with an average diameter of about 3μm.
[0067] Fourier-transform infrared spectroscopy (FTIR) was performed on the two groups of samples using a PerkinElmer Spectrum Two (PerkinElmer, USA). Figure 6 , the test results show that at 400cm -1 The strong absorption bands near 475 cm-1 are attributed to the stretching vibrations of In-O-In and In-OO-In bridge bonds. -1 The strong absorption band near 650cm -1 The peak near is attributed to the stretching vibration of InO6 octahedron. This is consistent with the previous study that the phonon energy of CaIn2O4 matrix is 500cm -1 From the spectroscopic point of view, CaIn2O4 oxide is a promising host material for lanthanide ion doping.
[0068] The down-conversion emission spectra were recorded using an Omni-k500 spectrometer (Zolix, China) under excitation of a 980 nm laser (MDL-III-980-2W, China). The temperature sensing characteristics were tested using a TAP-02 high temperature controller to control the sample temperature in the range of 303 K to 493 K. The temperature control accuracy was 0.1 °C.
[0069] Figure 7 (a) CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 3%Er 3+ 3D mapping of the down-conversion band projection of the sample in the temperature range of 303 to 493 K. At the same pump power, Er 3+ The ion intensity near 1550nm ( 4 I 13 / 2 → 4 I 15 / 2 ) and Yb3+ ions around 1000-1100nm ( 2 F 5 / 2 → 2 F 7 / 2 ) The emission intensity increases with increasing temperature. Studies have shown that CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 3%Er 3+ The sample produced a phenomenon of thermal enhancement of luminescence. Figure 7 (b) CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 3%Er 3+ Normalized spectra of the samples in the temperature range of 303 to 493 K. In the near-infrared region, Yb 3+ and Er 3+ The luminescence increases with increasing temperature.
[0070] Figure 8 (a)-(f) are CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 3%Er 3+ In the range of 303 to 493K, FIR, S A , S R Fig. FIR increases with increasing temperature, where I 1570 nm / I 1650 nm The maximum relative sensitivity is 1.975% K at 303 K. -1 .
[0071] Fig. 9 (a) CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 0.5%Ho 3+ 3D mapping of the down-conversion band projection of the sample in the temperature range of 303 to 493 K. At the same pump power, Ho 3+ The ion intensity near 1200~1250nm ( 5 I6→ 5 I8) and Yb3+ ions are around 1000-1100nm ( 2 F 5 / 2 → 2 F 7 / 2 ) The emission intensity increases with increasing temperature. Studies have shown that CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 0.5%Ho 3+ The sample produced a phenomenon of thermal enhancement of luminescence. Figure 7 (b) CaIn2O4:10%Yb 3+ / 0.2%Tm 3+ / 0.5%Ho 3+ Normalized spectra of the samples in the temperature range of 303 to 493 K.
[0072] Fig.10 (a)-(c) are CaIn2O4:10%Yb3+ / 0.2%Tm 3+ / 0.5%Ho 3+ Based on non-thermal coupling energy FIR, S A , S R Figure. I 1000~1125nm / I 1125~1250nm The maximum relative sensitivity is 9.802% K at 493 K. -1 In summary, CaIn2O4-based phosphors are promising biological window materials that can be used in the development of near-infrared biological fluorescent probes.
Claims
1. A method for preparing a fluorescent temperature measuring material for a biological window, characterized in that: The method comprises: weighing Yb2O3, Tm2O3, RE2O3 powders in molar ratio, wherein RE is Ho or Er, and the molar ratio satisfies: 10% Yb 3+ / 0.2%Tm 3+ / x%Er 3+ , x=1,2,3,4; or 10% Yb 3+ / 0.2%Tm 3+ / x%Ho 3+ , x=0.1, 0.3, 0.5, 0.7; Each component is mixed with nitric acid to prepare Yb(NO3)3 and Tm(NO3) 3、 RE (NO3)3 solution; Weigh CaCO3 and In(NO3)3·4.5H2O and mix them in a beaker, then drop Yb(NO3)3 and Tm(NO3) 3、 The RE (NO3)3 solution is stirred; Add complex citric acid and dilute with deionized water; The liquid was dried and evaporated to obtain a yellow xerogel, which was ground in an agate mortar with alcohol for 1 hour, and the ground powder was transferred to a ceramic crucible and placed in a high-temperature box-type electric furnace for calcination in two temperature stages; When RE=Er, x=1, the ratio of the weighed CaCO3 mass to In(NO3)3·4.5H2O and citric acid is 0.2942:2.1197:3.7065, which is the same as the added Yb(NO3)3 and Tm(NO3). 3、 The mass volume ratio of RE (NO3)3 solution g / ml is 0.2942:2.9397: 0.5879: 0.5879; When RE=Er, x=2, the ratio of the weighed CaCO3 mass to In(NO3)3·4.5H2O and citric acid is 0.2938:2.1053:3.7008, which is the same as the added Yb(NO3)3 and Tm(NO3). 3、 The mass volume ratio of RE (NO3)3 solution g / ml is 0.2938:2.93521: 0.5870: 1.1741; When RE=Er, x=3, the ratio of the weighed CaCO3 mass to In(NO3)3·4.5H2O and citric acid is 0.2933:2.0908:3.6951, which is the same as the added Yb(NO3)3 and Tm(NO3). 3、 The mass volume ratio of RE (NO3)3 solution g / ml is 0.2933:2.93070: 0.5861: 1.7584; When RE=Er, x=4, the ratio of the weighed CaCO3 mass to In(NO3)3·4.5H2O and citric acid is 0.2929:2.0765:3.6895, which is the same as the added Yb(NO3)3 and Tm(NO3). 3、 The mass volume ratio of RE (NO3)3 solution g / ml is 0.2929:2.92620: 0.5852: 2.3410; When RE=Ho, x=0.1, the ratio of the weighed CaCO3 mass to In(NO3)3·4.5H2O and citric acid is 0.2946:2.1328:3.7717, which is the same as the added Yb(NO3)3 and Tm(NO3). 3、 The mass volume ratio of RE (NO3)3 solution g / ml is 0.2946:2.9438: 0.5888: 0.2944; When RE=Ho, x=0.3, the ratio of the weighed CaCO3 mass to In(NO3)3·4.5H2O and citric acid is 0.2945:2.1299:3.7106, which is the same as the added Yb(NO3)3 and Tm(NO3). 3、 The mass volume ratio of RE (NO3)3 solution g / ml is 0.2946:2.9430: 0.5886: 0.8829; When RE=Ho, x=0.5, the ratio of the weighed CaCO3 mass to In(NO3)3·4.5H2O and citric acid is 0.2944:2.1271:3.7095, which is the same as the added Yb(NO3)3 and Tm(NO3). 3、 The mass volume ratio of RE (NO3)3 solution g / ml is 0.2944:2.9421: 0.5884: 1.4711; When RE=Ho, x=0.7, the ratio of the weighed CaCO3 mass to In(NO3)3·4.5H2O and citric acid is 0.2943:2.1242:3.7084, which is the same as the added Yb(NO3)3 and Tm(NO3). 3、 The mass volume ratio of RE (NO3)3 solution g / ml is 0.2943:2.9412: 0.5882: 2.0589.
2. The method for preparing a fluorescent temperature measuring material for a biological window according to claim 1, characterized in that: Yb(NO3)3, Tm(NO3) 3、 The concentrations of RE (NO3)3 solutions are: 0.1 mol / L Yb(NO3)3, 0.01 mol / L Tm(NO3) 3、 0.01mol / L Ho(NO3)3 or 0.05mol / L Er(NO3)3.
3. The material preparation method according to claim 1, characterized in that: The two temperature stages are: preheating and then sintering in the intelligent ceramic fiber muffle furnace. The temperatures are set to 500 °C and 1300 °C, and the times are set to 3 h and 6 h, respectively.
4. A fluorescent temperature measuring material applied to a biological window, characterized in that: According to the molar content, the temperature measuring material contains 10% Yb 3+ / 0.2%Tm 3+ / x%Er 3+ ,x=1, 2, 3, 4;or 10%Yb 3+ / 0.2%Tm 3+ / x%Ho 3+ , co-doped CaIn2O4 phosphors with x=0.1, 0.3, 0.5, 0.7.